Different Effects of Hypertension and Age on the Function of Large Conductance Calcium‐ and Voltage‐Activated Potassium Channels in Human Mesentery Artery Smooth Muscle Cells. Issue 9 (September 2016) - Cheng, Jun; Mao, Liang; Wen, Jing; Li, Peng‐Yun; Wang, Na; Tan, Xiao‐Qiu; Zhang, Xiao‐Dong; Zeng, Xiao‐Rong; Xu, Liang; Xia, Xian‐Ming; Xia, Dong; He, Kai; et al.
Abstract : Background: Large‐conductance calcium‐ and voltage‐activated potassium channels (BKC a channels) play important roles in the maintenance of vascular tone, and their dysregulation is associated with abnormal vascular relaxation and contraction. We tested the changes in BKC a channel properties in patients at different ages to assess the effects of hypertension and aging on the functional changes of BKC a channels. Methods and Results: Patch clamp was performed to detect the activities of BKC a channels in freshly isolated human mesenteric artery smooth muscle cells from younger patients (aged ≤45 years) without hypertension, older patients (aged ≥65 years) without hypertension, and older patients with hypertension. The expression of mRNA and protein from BKC a channels was evaluated by reverse transcription polymerase chain reaction and Western blot analysis, respectively. Results showed that the whole‐cell current density, spontaneous transient outward current, and Ca 2+ sensitivity of the artery smooth muscle cells were significantly decreased in the older patients with hypertension; the decreases were insignificant in the older patients without hypertension, although a clear tendency to have spontaneous transient outward current was detected in these patients. The expression of both mRNA and protein of BKC a subunits α and β1 was significantly decreased in the older patients with hypertension but not in the older patients without hypertension compared with the younger patients without hypertension. Conclusions: Our findings demonstrate for the first time that hypertension is an important factor for the pathological alteration of the properties of BKC a channels in human mesenteric artery smooth muscle cells, and aging itself may also be a factor in these changes in the cells.